Uso de senso comum no apoio a jogos narrativos para crianças em idade escolar - Silva, Marcos Alexandre Rose (2009)
This research describes how common sense knowledge can help to define and to tell stories in narrative games. In order to evaluate this possibility, it has been developed a Web narrative game, called Contexteller, which allows educators to teach some skills that are part of the student s education and life, such as: ways to express themselves and to work in group. Nowadays, there are several educational challenges to teach some skills at school. For instance, educators can not easily find a tool or activity in order to help them to work collaboratively with their students. Therefore, this game allows educators, as co-authors, to create the story taking into account their goals, pedagogical approach and the student s cultural reality. Through the game, they can get some information related to the student s values, culture and knowledge, i.e., student s common sense. Then, teachers can use common vocabulary before and during the narrative, considering myths, beliefs and knowledge of the students´ group and, consequently, enabling them not only to identify but also to get interested in collaborate with the teacher and the other students to develop the story. In order to observe the use of this game in an educational environment and collect the opinion of target group a study case, described in this thesis, was performed at a school in Itapira/SP.